Global Pentecostalism in the 21st Century - Hefner, Robert W., 1952- (Book collections on Project MUSE., 2013)
"This state-of-the-field overview of Pentecostalism around the world focuses on cultural developments among second- and third-generation adherents in regions with large Pentecostal communities, considering the impact of these developments on gender relations, citizenship, and the future of global Christianity itself. Leading scholars from anthropology, sociology, religious studies, and history present useful introductions to global issues and country-specific studies drawn from Latin America, Africa, Asia, and the former USSR."--Publisher's description.